Pengaruh Pemberdayan Kader Pencegahan Anemia terhadap Pengetahuan dan Sikap Pencegahan Anemia di Pondok Pesantren Sabilurrosyad Gasek Malang - Qonita Amalia; Siti Asiyah; Dimas Dwi Yoga Saputra (Yayasan Pendidikan Penelitian Pengabdian Algero, 2025)
Anemia is a condition of red blood cells with a small amount. Anemia is a disease that must get special attention, if it occurs in the long term it can have a major impact, one of which is stunting. Based on data from the Malang City Government in 2022, anemia in prospective brides in the Mulyorejo Health Center area ranks fourth, namely 278 or 32.8%. The purpose of this study was to analyze the effect of empowerment of anemia prevention cadres on the knowledge and attitudes of anemia prevention at Pondok Pesantren Sabilurrosyad Gasek Malang. This study used a quantitative method of Pre-experimental design with a One Group Pre Test-Post Test approach. The sample of this study was anemia prevention cadres totaling 30. The empowerment method is through FGD (Focus Group Discussion), cadre formation and cadre education regarding anemia prevention. Data collection techniques using questionnaires to measure the level of knowledge and attitudes of cadres. The results showed an increase in knowledge by 50% and an increase in attitude by 70%. Based on the results of hypothesis testing using the Wilcoxon Test, the value of knowledge and attitude p value 0.000 ≤ 0.05.This shows from the p value obtained there is an effect of interventions carried out by researchers on the knowledge and attitudes of cadres of the Sabilurrosyad Islamic Boarding School Gasek Malang.